A Byzantine Cranium from Jordan: A Case Study in Dental Anthropology - Abdulla Al-Shorman (Dental Anthropology Association, 2006)
This study describes a Byzantine cranium from an archaeological site in Jordan (Khirbit Yajuz). This case study illustrates severity of the multiple dental pathologies encountered and speculates on the cause of death. The 21-yers-old female of this study suffered multiple dental abscesses, where the accumulated pus reached the nasal cavity and the maxillary sinuses through a large fistula, probably causing septicemia that may have caused her early death. This case was selected from among similar cases from the site, and it illustrates an extreme, progressive state of caries and the absence of dental hygiene.